2017
DOI: 10.1245/s10434-017-5777-7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Preoperative Therapy on Short- and Long-Term Outcomes of Patients with Adenocarcinoma of the Ampulla of Vater

Abstract: Although these data do not support the routine administration of preoperative therapy to all patients with ampullary cancer, the delivery of preoperative therapy represents an alternative strategy that is associated with excellent short- and long-term outcomes and appears appropriate for a subset of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 39 publications
1
14
0
2
Order By: Relevance
“…11 However, this finding must be viewed in light of a possible selection bias: resectable patients with advanced disease were thought to possibly benefit from preoperative therapy due their comparatively higher disease burden. In fact, pathologic review of specimens following preoperative therapy and resection confirmed that poorly differentiated tumors were more common in patients with preoperative therapy compared to patients without preoperative therapy.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…11 However, this finding must be viewed in light of a possible selection bias: resectable patients with advanced disease were thought to possibly benefit from preoperative therapy due their comparatively higher disease burden. In fact, pathologic review of specimens following preoperative therapy and resection confirmed that poorly differentiated tumors were more common in patients with preoperative therapy compared to patients without preoperative therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In general, patients were considered candidates for up-front resection when they were medically fit and able to undergo macroscopically curative resection. For patients with 1) pre-existing comorbidity, 2) disease perceived to be biologically advanced due to one or more well-defined clinical parameters (e.g., regional lymphadenopathy, advanced T stage, indeterminate liver/lung lesions), or 3) treatment of disease believed to be pancreatic ductal adenocarcinoma on the basis of existing clinical workup, 11, 22, 23 preoperative therapy (chemotherapy alone or chemoradiation) was administered. 11, 12, 24 Preoperative chemotherapy primarily consisted of regimens containing fluorouracil, capecitabine, or gemcitabine administered for 4 to 6 months.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations